Characterization and Identification of Potent LMEs (Lignin Modifying Enzymes) Producing Fungi from Dang (Gujarat) - Bambharolia, R. P.; Vyas, Trupti K.; Deshmukh, A. J.; Damasia, D. M.; Vavdiya, P. A. (International Journal of Economic Plants, 2024)
Characterization and identification of potent LMEs (Lignin Modifying Enzymes) producing fungi from Dang (Gujarat) was conducted at Department of Plant Pathology, College of Agriculture, Navsari Agricultural University, Waghai in 2021-22, Fungal isolates LD1, LD4, LD5, LD9, LD15, LD19, LD20 and LD39 were screened for Lignin Modifying Enzymes (LME) on ABTS (2, 2 azinobis (3-ethylbenz-thiazoline)-6 sulphonate), Methyl orange and α- naphthol agar and observed that all the fungal strains showed color zone/clear zone on different indicator plates. However, fungal strain LD19 showed the highest potency index on both ABTS and methyl orange plates. Among the 8 selected fungal isolates, 5 produced all the three enzymes viz. laccase, lignin peroxidase (LiP) and manganese peroxidase (MnP), 2 produced two enzymes while 1 produced only one enzyme. Isolate LD19 had given maximum laccase activity at all the intervals and it was maximum at 6 DAI (206.74 U ml-1) followed by LD20 (144.79 U ml-1), LD4 (118.38 U ml-1) and LD15 (113.68 U ml-1). Maximum LiP activity was recorded in LD19 (1.314 U ml-1) at 8 DAI followed by LD1 (0.903 U ml-1) and it was lowest in LD39 (0.725 U ml-1). Maximum MnP activity was recorded in LD19 (428.65 U ml-1) at 8 DAI followed by LD39 (308.13 U ml-1), LD15 (290.18 U ml-1), LD4 (262.16 U ml-1) and MnP activity was not detected in LD1 and LD5. The highest LMEs were observed in LD19. Potential LMEs producing fungi LD19 wasidentified as Schizophyllum commune, by morphological, microscopic characteristics and molecular methods and submitted to NCBI GenBank database with accession numbers MW720154.